Parallel Models of Reading and Numerical Cognition. - Hall, Garret J.; van Dijk, Wilhelmina; Chow, Jason C.; Borkenhagen, Matthew J. Cooper (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2025)
Reading and math are related due to many codeveloping skills. Historically, theorizing in these two areas has progressed separately, despite well-documented empirical evidence for a range of shared underlying developmental processes subserving these learning domains. The purpose of this article was to describe the links between the Triple Code Model, an influential model of numerical cognition, and the Triangle Framework, a dominant model of learning to read. We describe several parallels between the theoretical models and discuss how the cognitive mechanisms posited by the Triangle Framework might be used to understand the commonalities in learning processes across these learning domains. In particular, we discuss how the cognitive mechanisms implemented in the Triangle Framework can be used to understand linguistic aspects of numerical cognition, specifically, learning the connections among numerals (e.g., 24) and spoken words (e.g., twenty-four), and linking those to semantic representations of magnitude. Following from these commonalities between the two models, we discuss several ways that interdisciplinary work integrating both models can benefit math cognition research.